The mediating role of perceived emotional intelligence: examining the impact of affective job satisfaction on organizational identification among Chinese technological workers - Lai, Yuege; Gao, Ge; Du, Baiyan (Frontiers in Psychology, 2024)
Breaking new ground in the exploration of workplace dynamics, this study pioneers an investigation into the mediating role of perceived emotional intelligence (PEI) in the relationship between affective job satisfaction and organizational identification among Chinese technological workers. This novel focus addresses a critical gap in existing research, particularly in understanding the psychological underpinnings within this specific cultural and professional context. Involving 392 workers aged 23 to 60, our research offers a comprehensive examination of how the three subdimensions of PEI – attention, clarity, and emotional repair – interact with job satisfaction to influence organizational identification. Through extensive questionnaires, we assessed these subdimensions alongside affective job satisfaction and the workers' identification with their organization. Our findings reveal a significant, positive correlation between job satisfaction and all PEI subdimensions. Notably, while emotional clarity and emotional repair showed a positive relationship with organizational identity, attention did not. Further analysis highlighted the substantial direct impact of Affective Job Satisfaction on Organizational Identification, with emotional clarity and emotional repair playing critical mediating roles. These insights illuminate the unique function of Perceived Emotional Intelligence as a mediator and enhancer in the relationship between job satisfaction and organizational commitment. The results underscore the necessity of integrating strategies to cultivate emotional intelligence in the workplace, potentially leading to stronger organizational ties and improved overall worker well-being. By shedding light on these complex psychological mechanisms, our study not only enriches the theoretical landscape but also offers practical guidance for fostering healthier, more productive work environments.